Distinguishing Spinal Cancer and Degenerative Disease: Enhancing Diagnosis and Treatment Outcomes in Plasmacytoma - -, Liana Alviah Saputri; Riyanto Sofyan, Henry; Aninditha, Tiara; Savitri, Irma; Saekhu, Mohammad; Kusuma, Radius (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2026)
Introduction: Spinal lesions commonly exhibit overlapping clinical presentations and imaging characteristics, which can obscure the distinction between malignant and degenerative etiologies. This diagnostic ambiguity may lead to delayed or inappropriate treatment, particularly in uncommon neoplastic entities such as plasmacytoma, a solitary manifestation of plasma cell dyscrasia that often involves the spine. Case Report: We report the case of a 63-year-old male presenting with one month of persistent back pain, progressive bilateral lower limb weakness, and tingling sensations radiating from the inguinal region to the toes. Imaging studies revealed bilateral pedicle destruction at the L2 and L5 vertebrae, along with significant spinal canal and foraminal stenosis. The patient underwent decompression surgery, and histopathological analysis of the lesion confirmed the diagnosis of plasmacytoma. Discussion: Spinal plasmacytoma is a rare neoplastic condition that can clinically mimic degenerative spine disorders, often leading to delays in diagnosis and treatment. Symptoms such as chronic back pain, radiculopathy, and motor weakness are commonly attributed to more prevalent degenerative pathologies, particularly in older adults. Back pain in individuals with a history of malignancy serves as a crucial warning sign, prompting clinicians to urgently assess for potential metastatic disease in the spine. Conclusion: Increased awareness and a high index of suspicion are crucial when evaluating spinal lesions. Pain should be considered a key red flag warranting prompt assessment for possible spinal malignancy. Early diagnosis is critical, as it directly affects therapeutic decisions and overall prognosis.